Analysis the convensional insurance according to shariah principles / Siti Hamizah Ismail - Ismail, Siti Hamizah (2019)
Conventional insurance is an insurance system that has been used by Malaysian society for a long time. The purpose of this study is to examine conventional insurance according to shariah principles. The problems statement such as have elements of non-compliant shariah and the reasons for the implementation of the prohibition against this system are also discussed in this study. The objective of this study is to identify the elements of conventional insurance and to analyze the conventional insurance system according to shariah principles. This study uses the method of collecting data through interview and documents analysis and library to get the right information about conventional insurance products according to shariah principles. The findings show that there are many elements that are not justified by the shariah in the implementation of this conventional insurance. The results of this study show that conventional insurrection gives a lot of negative impressions especially to Muslims. Therefore, Muslims are forbidden to involve themselves in illegal matters such as usury or directly or indirectly.